IMAM SYAFI'IE DAN PESANTREN - Saiful Anam (Dirosat : Journal of Islamic Studies, 2016)
Imam Syafi’ie was a Muslim innovator. It was proofed by old statement and new statement which was known in two his life. Imam Syafi’ie could be called as a Muslim Intellectual who was the most familiar around muslim’s society in Indonesia. Because his name was so closer with them, indeed it was become the name of school or Islamic school in Indonesia, such as; Syafi’iyah or Salafiyah Syafi’iyah etc. in his life, Imam Syafi’ie wrote about 200 book, especially in fiqh.